Life on the leash : a novel - Schade, Victoria (Pocket Books, 2022)
"Cora Bellamy is a woman who thrives on organization. She's successfully run her own dog training business for years, perfectly content with her beloved rescue pitbull as the main man in her life. She's given everything to her business, and her lack of social life (or slobber-free clothes) has been completely worth it. But all that changes when she meets Charlie Gill, the hottest client she's ever had. The only problem? Charlie's taken. Luckily, Cora's new friend--the sweet, lovably geeky Eli Crawford--is always there to help Cora with her problems, including her love life. That's why she's shocked to realize that even as things start heating up with Charlie, there might just be a more-than-friends spark between her and Eli, too. As Cora's life gets more tangled up than a dogwalker's leashes--and as she prepares to audition for a dog-training TV show that may irrevocably change her entire life--she has to figure things out before it all goes straight to the dogs." --